2011
DOI: 10.1002/ana.22355
|View full text |Cite
|
Sign up to set email alerts
|

Point‐of‐care laboratory halves door‐to‐therapy‐decision time in acute stroke

Abstract: Currently, stroke laboratory examinations are usually performed in the centralized hospital laboratory, but often planned thrombolysis is given before all results are available, to minimize delay. In this study, we examined the feasibility of gaining valuable time by transferring the complete stroke laboratory workup required by stroke guidelines to a point-of-care laboratory system, that is, placed at a stroke treatment room contiguous to the computed tomography, where the patients are admitted and where they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
68
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 22 publications
0
68
0
1
Order By: Relevance
“…In prehospital stroke treatment, neuroradiological competence may be provided in several ways, for example, by the presence of specifically trained physicians in the ambulance [3,5] or by telemedicine support for the MSU team so that images can be evaluated by experts in the hospital. In the United States, the latter approach has recently been shown to be very reliable because of the widespread availability of 4G connectivity and the prioritization of EMS telecommunications [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In prehospital stroke treatment, neuroradiological competence may be provided in several ways, for example, by the presence of specifically trained physicians in the ambulance [3,5] or by telemedicine support for the MSU team so that images can be evaluated by experts in the hospital. In the United States, the latter approach has recently been shown to be very reliable because of the widespread availability of 4G connectivity and the prioritization of EMS telecommunications [13].…”
Section: Discussionmentioning
confidence: 99%
“…A mobile stroke unit (MSU), incorporating all the tools necessary for guideline-adherent and etiology-specific treatment directly at the emergency site, was proposed in 2003 [2] and shown to facilitate prehospital thrombolysis in 2009 [3]. The MSU is an ambulance that includes CT scan for multimodal imaging with a quality comparable to that of a stationary CT scanner [4]; a point-of-care laboratory system [5]; and a telemedicine connection to the hospital [2,3]. A first randomized trial of the MSU found a 50% reduction in delay from stroke onset to treatment [6].…”
Section: Introductionmentioning
confidence: 99%
“…Although practices such as direct to CT 21,23-25 and avoiding delay waiting for coagulation tests [26][27][28][29] in nonanticoagulated stroke patients gained some acceptance from baseline to 1-year assessment, 3 best practice strategies (earlier stroke team activation, premixing tPA, 23,25 and streamlined consent processes) 30 were newly implemented at a majority of sites. Although we cannot ascribe the causality of best practice implementation and individual patient care, we speculate that these key practice changes were mediators of the aggregate improvement we observed.…”
Section: Discussionmentioning
confidence: 99%
“…This new treatment paradigm combining a fast-acting reversal agent with remote physician evaluation, on-site imaging, and laboratory testing for the first time affords ultraearly reversal of warfarin effect. Walter et al 6 reported validation of point-of-care laboratory testing in acute stroke setting and showed reduction time to ischemic stroke thrombolysis. We are also currently correlating point-of-care test results on MSTU with hospital laboratory results.…”
Section: Discussionmentioning
confidence: 99%